Sapphire Rapids: The Next-Generation Intel Xeon Scalable Processor - Nassif, Nevine; Munch, Ashley O.; Molnar, Carleton L.; Pasdast, Gerald; Lyer, Sitaraman V.; Yang, Zibing; Mendoza, Oscar; Huddart, Mark; Venkataraman, Srikrishnan; Kandula, Sireesha; Marom, Rafi; Kern, Alexandra M.; et al. (Digest of technical papers - IEEE International Solid-State Circuits Conference, 2022)
Sapphire Rapids (SPR) is the next-generation Xeon® Processor with increased core count, greater than 100MB shared L3 cache, 8 DDR5 channels, 32GT/s PCIe/CXL lanes, 16GT/s UPI lanes and integrated accelerators supporting cryptography, compression and data streaming. The processor is made up of 4 die (Fig. 2.2.7) manufactured on Intel 7 process technology which features dual-poly-pitch SuperFin (SF) transistors with performance enhancements beyond 10SF,>25% additional MIM density over SuperMIM and a metal stack with a 400nm pitch routing layer optimized for global interconnects. This layer achieves ~30% delay reduction at the same signal density and is key for achieving the required latency. The core provides better performance via a programmable power management controller. New technologies include Intel Advanced Matrix Extensions (AMX), a matrix multiplication capability for acceleration of AI workloads and new virtualization technologies to address new and emerging workloads.